Efektivitas Kombinasi Ekstrak Limbah Kulit Bawang Merah dan Kulit Bawang Putih serta Serai sebagai Pestisida Organik terhadap Serangan Ulat Jerman (Tenebrio molitor) pada Tanaman Selada (Lactuca sativa) - Faturahman, Rizal; Yasifa, Nurul Ajlina; Setyani, Arisa; Febrianty, Arlindi (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Agriculture plays a crucial role in sustaining food security and the economy in Indonesia. Lettuce (Lactuca sativa), especially green curly lettuce, is a promising horticultural crop due to its relatively short growth period and high nutritional value. This study aimed to evaluate the effectiveness of organic pesticides derived from shallot peel, garlic peel, and lemongrass in controlling pest damage on lettuce. In this study, we conducted an experiment using Tenebrio molitor (mealworms) as a simulated pest attack on lettuce plants. The experiment used a Completely Randomized Design (CRD) with four treatments: P0 (no pesticide), P1 (shallot peel), P2 (shallot + garlic peel), and P3 (shallot + garlic peel + lemongrass), each replicated five times. Damage levels were measured organoleptically and analyzed using ANOVA and LSD tests at a 5% significance level. The P3 treatment resulted in the lowest leaf damage (1.63%), while the P0 treatment showed the highest (90%). The effectiveness of the organic pesticide is attributed to active compounds such as phenolics and flavonoids in shallot peel, allicin in garlic, and citronellal in lemongrass, which possess insecticidal properties. These findings demonstrate that combining these organic materials can synergistically suppress pest activity. In conclusion, organic pesticides formulated from agricultural waste materials offer a sustainable and eco-friendly alternative to chemical pesticides in lettuce cultivation.